Pengaruh Kinerja Lingkungan Terhadap Nilai Perusahaan dan Kinerja Keuangan - Sri Tjahjono, Mazda Eko (Lembaga Penerbitan Unversitas Esa Unggul, 2013)
AbstractThe objective of this study is to examine the influence of enviromental performance to firm value with financial performance as intervening variable. This study takes sample from 31 companies in the Indonesian Stock Exchange, which were published in financial report from 2010-2011. The method of analysis of this research used multi regression and path analysis. The results of this study show that (1) enviromental performance had significant influence to financial performance, (2) enviromental performance had not significant influence to firm value, (3) financial performance had significant influence to firm value, (4) enviromental performance had significant influence on the financial performance of the firmâ€™s value through. Financial performance is an intervening variable in the relationship between environmental performance and the audit committee of the firm's value.Keywords: corporate governance, enviromental performance, the presence of board independent of Â director